PENGEMBANGAN MODUL Bryophyta DI KAWASAN AIR TERJUN BATU RAMBAT SEBAGAI SUMBER BELAJAR BIOLOGI - Rahmawati, Tika; Dewi, Asih Fitriana; Yudiyanto, Yudiyanto; Suhendi, Suhendi (JURNAL BIOEDUCATION, 2022)
Student learning in the current era is very different from previous years, as a result of the COVID-19 pandemic, learning is shifted at home. Students must get used to not relying on the teacher so that they can try to make decisions and ways to solve problems individually. This change in learning makes students look for additional material to better understand learning even though learning is currently using distance learning. The development of new innovations in learning is currently very necessary. Creating learning resources can be done by utilizing the potential of the natural surroundings as well as introducing students to love the surrounding nature. One of the natural surroundings that has the potential as a source of learning in biology learning is the Batu Rambat waterfall in which there are Bryophyta (mosses) related to biological material. The purpose of this study was to develop the Bryophyta module in the Batu Rambat waterfall area as a learning resource for class X high school students based on the feasibility of the module with a small group trial limit. This study uses the Research and Development method with a 4D model carried out with the define stage, the design stage, the develop stage, and the disseminate stage. The results of the module feasibility test carried out by material expert validation obtained results of 91% with the "very good" category. While the results of media expert validation obtained results of 95% with the "very good" category. Based on the validation of material experts and media experts that the developed module is feasible to be tested on teachers and students in small groups. The teacher's response assessment obtained a result of 87% in the "very good" category and the response assessment of 10 students obtained a score of 88.8% in the "very good" category. With the assessment by the teacher and students in small groups, it is known that the module is suitable for use in the very good category. The learning resource for the Bryophyta module that has been developed is appropriate to be used as a learning resource in biology learning and as a reference so that it gains broad insight.